Green jobs in cities: Challenges and opportunities in African and Asian intermediary cities - Wolfgang Scholz; Michael Fink (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
Cities account for approximately 70 per cent of global energy consumption and about 75 percent of greenhouse gas emissions due to the density of economic activities and infrastructure and their often path -dependent development patterns. While this makes cities vulnerable to the impacts of climate change and causes of biodiversity loss and environmental degradation, cities can also play an important role in taking on climate change mitigation and adaptation actions. Cities adopting a green transformation process can minimise their environmental impact and maximise opportunities to improve and support the natural environment. Topics to address are energy efficiency and reduction of non-renewable energy sources to reduce their carbon footprint; actively support waste reduction and management; establish green and resilient infrastructure ; encourage nature-based solutions ; enhance the efficiency of new buildings; encourage low-carbon transport; and improve water cycle management. Also, these fields will lead to a greener urban economy, create more green jobs - or respectively change jobs towards becoming green - and deliver improved quality of life outcomes for residents. The current pandemic situation and the need for a quick COVID -19 recovery has created new challenges, but also the potential for a green and just recovery 'to create jobs and improve health in cities while limiting warming to 1.5°C (C40 Cities Climate Leadership Group, 2021). Also, the OECD (2020) evaluates that 'the economic stimulus packages and recovery plans that governments are now putting in place have the potential to create a recovery that is both green and inclusive.' [...]
Keywords: 330; Umweltberufe; Stadt; Nachhaltige Stadtentwicklung; Afrika; Asien